Improving materials management on construction projects - Kasim, Narimah (2008)
An essential factor adversely affecting the performance of construction projects is the improper handling of materials during site activities. Materials management is made problematic by materials shortages, delays in supply, price fluctuations, damage and wastage, and lack of storage space. In addition, paper-based reports are mostly used to record and exchange information related to the materials component within a supply chain which is problematic, error-prone, and inefficient. Generally, modern technologies are not being adequately used to overcome human error and are not well integrated with project management systems to make the tracking and management of materials easier and faster. Thus, this research focuses on the development of a mechanism to improve materials management on construction projects through the integration of materials tracking and resource modelling systems. A multi-facetted research approach was adopted. Initially, a literature review on materials management process in the construction project was conducted. This was followed by case studies involving six construction projects in order to investigate current practice in materials management to establish key problem areas and elements of good practice. The case studies also explored the requirements for integrating materials management and resource modelling in project management systems. The case study findings underpinned by literature results were used to develop a real-time framework for integrating RFID-based materials tracking and resource modelling. The framework was encapsulated in a computer-based prototype system based on Microsoft Visual Basic.NET. The prototype system was developed by amalgamation of all the software and hardware chosen such as MS Access (database system), MS Project (resource modelling) and RFID (automated materials tracking) to provide the mechanisms for integrating materials management and resource modelling in the construction industry. Evaluation of the prototype system was carried out by a series of interviews with industry practitioners to assess its appropriateness and functionality. It also established the skills and other requirements for the effective use of the real-time materials tracking system. The evaluation established that the prototype system demonstrated many benefits and is suitable for use in materials tracking and inventory management processes. It is concluded that the prototype system developed can improve materials management on construction projects, particularly with regard to materials tracking and integrating materials utilisation with the resource modelling subsystem in project management applications. Adoption of the approaches suggested in the thesis will enable the construction industry to improve the real-time management of materials on sites, and hence improve project performance.